The Antioxidant Activity of Red Fruit Extract (Pandanus conoideus L.) From Nabire Papua - Migau, Natalina; Mokosuli, Yermia; Wurarah, Masje; Manampiring, Nonny (Indonesian Biodiversity Journal, 2024)
Red fruit (Pandanus conoideus Lam) is a native Papuan plant which has been used by indigenous Papuan people as a medicinal plant. Papuan people believe that red fruit has a broad spectrum of pharmacological activity. This research aims to obtain antioxidant activity, namely reducing DPPH free radicals from Papuan red fruit ethanol extract. Samples of red fruit obtained from Nabire Papua. After determination, the red fruit is extracted using the maceration method. The ethanol extract of red fruit was then used for the DPPH antioxidant test method. The results showed that the ethanol extract of red fruit contains phenolic compounds: flavonoids, tannins; and steroids in high intensity. Ethanol extract of red fruit has very strong antioxidant activity (46.99 ppm; R2=0.99). Ethanol extract of Papuan red fruit has potential as a source of bioactive natural antioxidants.